Analysis of Vaccination of Children and Its Timing Against Infections from the National Immunization Schedule in the Volga and Far Eastern Federal Districts of Russian Federation: Cross-Sectional Study - Radima A. Mukozheva; Tatyana V. Kulichenko; Tatyana V. Vilchanskaya; Olga V. Romanova; Mariya A. Lazareva; Juliya S. Lashkova; Inga V. Artemova (Вопросы современной педиатрии)
Background. Delayed vaccination increases the period of vulnerability of children to vaccine preventable diseases. It is associated with higher risk of infectious morbidity and outbreaks (including previously controlled diseases).Objective. Our aim was to study the vaccination of children and its timing according to the National Immunization Schedule (NIS) in Russian Federation regions.Methods. We have performed retrospective cross sectional study. Data from 2838 maps of preventive vaccinations (form No 063/y) in children of 2015-2017 years of birth from 18 subjects of Volga and Far Eastern federal districts, as well as data from the state federal statistical monitoring forms No 6 “Information on children and adults populations vaccinated against infectious diseases" in 2016-2019 in the same subjects of Russian Federation was analyzed.Results. The proportion of children vaccinated according to the NIS varies from 8% to 87.1% (depending on the vaccine type). 51.5-94.5% of children are vaccinated timely to decreed dates according to the age criteria used in Form No 6. Whereas, more than 95% of children were considered vaccinated against infections from the NIS list (except pneumococcal infection) according to official statistics. Significant regional differences in vaccination of children and its timing were revealed.Conclusion. Significant numbers of children remains unvaccinated or are or untimely vaccinated against infections from the NIS list. At the same time, there is considerable difference between the data about vaccination and its timing received from the analysis of primary medical documentation and from the state federal statistical monitoring forms.